Personalized Nutrition: How to make it possible? - Witri Ardini; Saptawati Bardosono (World Nutrition Journal, 2019)
The advancing of economic and technology in the last 1–2 centuries that characterized by industrialization, urbanization, and globalization have changed human lifestyle worldwide. Abundance of food and the ease of getting it, the availability of calorie-dense processed foods, changes in dietary patterns, and sedentary lifestyles force the rapid accretion of the incidence of obesity and non-communicable diseases such as type 2 Diabetes mellitus, cardiovascular diseases (CVD), and cancer. Non communicable diseases (NCDs) are the leading cause of death worldwide, and one of the major health challenges of the 21st century.1 In 2016, NCDs were responsible for 71% (41 million) of the 57 million deaths which occurred globally. The major NCDs responsible for these deaths included cardiovascular, cancers, chronic respiratory diseases, and diabetes.2 Many epidemiological, observational, and clinical studies have shown that nutrition, as the main environmental factor, plays a pivotal role in these high-cost degenerative diseases.